IMPROVING STUDENTS’ OUTCOME USING GEOGEBRA INTERACTIVE MEDIA IN LEARNING DERIVATIVES - Lumbantobing, Happy (Journal of Honai Math, 2020)
The purpose of this research is to consider the benefit of applying GeoGebra interactive media to improve student achievement in learning derivatives. This study was experimental research using counterbalance design. The population of the study was four classes of grade XI students of SMA Negeri 3 Jayapura academic year 2018/2019 consisting of 122 students. Purposive sampling was applied in this study to get two experimental classes with the number of students were 22 and 26 respectively. In both experimental groups received the same treatment which were learning using GeoGebra interactive media and learning without using GeoGebra interactive media which applied orderly. This process was implemented four times at both classes interchangeably. The data of the study was collected from participant’s pretest and posttest at every learning treatment. Data was analyzed using Wilcoxon Signed test with the significance level (two-tailed) of 0.05. The result of the study shows that there are significant differences in learning outcomes of the two types of learning. The learning process which was designed using GeoGebra interactive media obtained the superior learning outcomes.